From “death” to “life” – דָּם in the psalms: a lexical-semantic-cultural survey, with special reference to the translation of “blood” in a western and an African setting - Wendland, Ernst (Journal for Semitics, 2016)
After a brief lexical-semantic summary of the principal senses of דָּם in the Hebrew Bible (HB), our focus shifts to this word’s 21 occurrences in the Psalms. How widely and diversely was the notion of “blood” employed in the psalmists’ manifold prayers to the Lord? We then consider the practice of translation in two greatly contrasting sociocultural settings – Western versus African. What are some of the main challenges that translators confront when they attempt to convey the distinct “meanings” of דָּם meaningfully – with functionally equivalent content, intent, impact and appeal – in these two disparate contexts? In a Western setting, as expressed in English, the biblical, symbolically sacred understanding of “blood” is virtually non-existent, thus necessitating significant paratextual supplementation, whereas in an African linguistic environment, Chichewa for example, the ancient symbolical sense of “blood” and its contemporary connotations remain so powerful that it requires great care in translation in order to avoid possible misunderstanding or offense in the vernacular text. In the latter case and in certain Psalmic passages, it turns out that instead of some expression relating to “death”, one that rather conveys the notion of “life” may well be more accurate and acceptable, especially when uttered in prayer or praise to the Lord.
free